TINJAUAN YURIDIS TINDAKAN DELISTING OLEH BURSA EFEK INDONESIA DAN PERLINDUNGAN PEMEGANG SAHAM (STUDI KASUS: PT. BERAU COAL ENERGY, Tbk.) - Louise Ruselis Sitorus (Dialogia Iuridica, 2019)
A public-listed company essentially is required to be aware of all of its consequences and obligations inter alia protecting the interests of minority shareholders, conducting information disclosure and acting in accordance with relevant national laws and regulations. If such obligations are neglected, the company may jeopardize its existence in the stock exchange listing. It may be delisted. A delisted company has obligations to convey delisting decision to their investors as information disclosure and acting in accordance with relevant national laws and regulations. However, a delisted company does not automatically turn its status from public-listed company to Private Company. As long as the company runs with fulfilled requirements to become a public-listed company, it still bears the aforementioned obligations.Â There is a wrong assumption that a delisted company will be harm the shareholders. delisting company prevents an even greater loss of investors from letting investors invest in unprofitable companies. Whereas investors invest their shares with the aim to gain profits. Investors can also make various efforts to get protection.Â Keywords: Capital Market, Delisting, Public-Listed Company